2019
DOI: 10.1088/1748-9326/ab55fc
|View full text |Cite
|
Sign up to set email alerts
|

Significantly lower summer minimum temperature warming trend on the southern Tibetan Plateau than over the Eurasian continent since the Industrial Revolution

Abstract: Summer temperature dominates environmental degradation and water resource availability on the Tibetan Plateau (TP), affecting glacier melting, permafrost degradation, desertification and streamflow, etc. Extending summer temperature records back before the instrumental period is fundamentally important for climatic and environmental studies over long timescales. By pooling 39 tree-ring width records from the TP that show significant (P<0.05) correlations with the summer (June-August) minimum temperature (Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…For example, snow cover increased over the southwestern Tibetan Plateau leads to the annual temperature has decreased by 0.15°C/decade during 2001-2015 (Guo et al 2019b). Third, Shi et al (2019) found that obviously lower summer minimum temperature warming trend on the southern Tibetan Plateau (2.3×10 −3°C /year) than over the Eurasian continent (5.1×10 −3°C / year) from 1850 to 1950 could be due to increased evaporative cooling. However, there are temporal and spatial differences in the degree of evaporative cooling at different altitudes.…”
Section: Discussionmentioning
confidence: 93%
“…For example, snow cover increased over the southwestern Tibetan Plateau leads to the annual temperature has decreased by 0.15°C/decade during 2001-2015 (Guo et al 2019b). Third, Shi et al (2019) found that obviously lower summer minimum temperature warming trend on the southern Tibetan Plateau (2.3×10 −3°C /year) than over the Eurasian continent (5.1×10 −3°C / year) from 1850 to 1950 could be due to increased evaporative cooling. However, there are temporal and spatial differences in the degree of evaporative cooling at different altitudes.…”
Section: Discussionmentioning
confidence: 93%
“…It is noteworthy that the differences between W08 and this study emphasize the fact that the response of the atmosphere and hence the ASM climate are sensitive to the location of the warming within the TP with the caveat that the experiments in the two studies are not identical. Furthermore, the TP warming may not occur homogeneously in the future (Shi et al 2019). A more detailed analysis will thus be needed to affirm the robustness of these results.…”
Section: Discussionmentioning
confidence: 95%
“…Another major implication is that this study emphasizes the need for a better representation of the glaciers in climate models. In a recent study, analyzing the summertime warming trend, Shi et al (2019) reported that the CMIP5 models overestimate the southern TP warming rate in historical simulations. Based on our study, the possibility of this overestimated warming could be a contributor to CMIP5-simulated systematic dry bias over the ASM domain (Narapusetty et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, trends were computed for each pixel in the satellite NDVI data and gridded precipitation and temperature data. Pixel-wise correlations between NDVI and climatic variables were calculated from aggregated annual and seasonal time-series data over a 34-year period, similar to the analysis proposed by [ 53 , 66 , 67 ]. NDVI values were spatially averaged over the UJRB and all vegetation types were used to extract NDVI values of the specific LULC classes.…”
Section: Methodsmentioning
confidence: 99%